IL-27 induces an IFN-like signature in murine macrophages which in turn modulate colonic epithelium - Andrews, Caroline; McLean, Mairi H.; Hixon, Julie A.; Pontejo, Sergio M.; Starr, Tregei; Malo, Courtney; Cam, Margaret; Ridnour, Lisa; Hickman, Heather; Steele-Mortimer, Olivia; Wink, David A.; Young, Howard A.; et al. (Frontiers in Immunology, 2023)
Mucosal delivery of IL-27 has been shown to have a therapeutic benefit in murine models of inflammatory bowel disease (IBD). The IL-27 effect was associated with phosphorylated STAT1 (pSTAT1), a product of IL27 receptor signaling, in bowel tissue. To determine whether IL-27 acted directly on colonic epithelium, murine colonoids and primary intact colonic crypts were shown to be unresponsive to IL-27 in vitro and to lack detectable IL-27 receptors. On the other hand, macrophages, which are present in inflamed colon tissue, were responsive to IL-27 in vitro. IL-27 induced pSTAT1 in macrophages, the transcriptome indicated an IFN-like signature, and supernatants induced pSTAT1 in colonoids. IL-27 induced anti-viral activity in macrophages and MHC Class II induction. We conclude that the effects of mucosal delivery of IL-27 in murine IBD are in part based on the known effects of IL27 inducing immunosuppression of T cells mediated by IL-10. We also conclude that IL-27 has potent effects on macrophages in inflamed colon tissue, generating mediators that in turn act on colonic epithelium.